Factors influencing consumer preferences towards fast food restaurant / Nur Athirah Baharudin - Baharudin, Nur Athirah (2020)
This undergraduate project is based on the previous researcher which is the research as the secondary data. This topic also is the currently situation which is the factors influencing consumer towards fast food. As be knowing the fast food is one of the popular foods that be choosing by the consumer. Tan Lee Ying (2011) defined that fast food is one type of food able to prepare in short time period and sell to customer in reasonable price. In this study, will know that what the factor influencing the consumer towards fast food and the relationship between the independent variables and dependent variables. In chapter 1, will be know the introduction, background of the study, the problem statement, research objectives and the questions, the framework of the independent and dependent variables, hypothesis, significance and limitation of the study and the definition of the important key. For the chapter 2, will study about the literature review for every key point or term that be explain. Meanwhile, in chapter 3 basically will study about the methodology that be choosing by the researcher which is the secondary data. Lastly, chapter 4, the researcher will conclude all the chapter from the chapter 1 to chapter 4 and make the recommendations.